Using Compassion Focused Therapy as an adjunct to Trauma-Focused CBT for Fire Service personnel suffering with trauma-related symptoms. (29th November 2016) - Beaumont, Elaine; Durkin, Mark; McAndrew, Sue; Martin, Colin R.
Abstract: Individuals working for the emergency services often bear witness to distressing events. This outcome study examines therapeutic interventions for Fire Service personnel (FSP) experiencing symptoms of trauma, depression, anxiety and low levels of self-compassion. This study aims to investigate the effectiveness of using Compassion-Focused Therapy (CFT) as an adjunct to Trauma-Focused Cognitive Behavioural Therapy (TF-CBT) in reducing symptoms of trauma, anxiety and depression and increasing self-compassion. A convenience sample ( n = 17) of participants, referred for therapy following a traumatic incident, were allocated to receive 12 sessions of either TF-CBT or TF-CBT coupled with CFT. The study employed a repeated-measures design. Data were gathered pre- and post-therapy, using three questionnaires: (1) Hospital Anxiety and Depression Scale; (2) Impact of Events Scale-R; (3) Self-Compassion Scale – Short Form. TF-CBT combined with CFT was more effective than TF-CBT alone on measures of self-compassion. Significant reductions in symptoms of depression, anxiety, hyperarousal, intrusion and avoidance and a significant increase in self-compassion occurred in both groups post-therapy. The study provides some preliminary evidence to suggest that FSP may benefit from therapeutic interventions aimed at cultivating self-compassion. Further research is warranted using a larger sample size and adequately powered randomized controlled trial, to detect statistically significant differences and to negate the risk of confound due to low numbers resulting in significant differences between groups at baseline. Using CFT as an adjunct to TF-CBT may help FSP, who bear witness to the distress of others, cultivate compassion for their own suffering.